Serial 3 T magnetic resonance imaging during cabergoline treatment of macroprolactinomas. (April 2015) - Kurosaki, Masamichi; Kambe, Atsushi; Watanabe, Takashi; Fujii, Shinya; Ogawa, Toshihide
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: Cabergoline is the treatment of choice for prolactin (PRL)-producing pituitary adenomas, because of its efficacy in normalizing PRL levels, and inducing tumor shrinkage. The clinical use of 3 T magnetic resonance imaging (MRI) for neuroimaging has rapidly expanded in recent years. In particular, T2-weighted imaging (T2WI) provides high anatomical and contrast resolution. Patients and methods: In this study, serial 3 T MRI with T2WI was utilized during cabergoline treatment of 10 patients with macroprolactinomas. Cabergoline was started at a standard weekly dosage and incrementally adjusted on individual posttreatment PRL values. Results: MRI confirmed tumor shrinkage in all patients during cabergoline treatment. Cabergoline normalized hyperprolactinemia in all but one patient. In six of 10 patients, distinct low-signal-intensity areas were evident throughout the adenomas on T2WI. In four of those six patients, massive low-signal-intensity areas appeared at 1–4 months, after which tumors decreased in size by over 80%. These findings in the early phase of prolactinoma treatment predicted pronounced regression or near-complete disappearance of the tumor. Reduction of T2 intensity possibly reflected dehydration due to diffuse hemorrhage in the adenomas. Conclusion: T2-weighted 3 T MR images are valuable for assessing and monitoring cabergoline treatment of macroprolactinomas.